Upaya Peningkatan Kemampuan Masyarakat dalam Pengendalian Kegawatdaruratan Gangguan Kardiovaskuler melalui Kegiatan Screening, Monitoring dan Treatment pada Masyarakat Beresiko di Puskesmas Kuranji dan Puskesmas Belimbing Padang - Hendri Budi; Efitra; Metrilidya; Mitriya Rika (CV. CENDIKIA JENIUS INDONESIA, 2023)
Cardiovascular emergencies are diseases that are feared by our society because their attacks can cause death. Approximately 50% of patients who present with chest pain have a history of acute coronary syndrome (ACS). This community service activity aims to increase the community's ability to control coronary heart disease and stroke. The method of this service is conducting screening, education, demonstrations and simulations to improve community skills in terms of early detection and home care for coronary heart disease and stroke as well as monitoring and monitoring coronary heart disease and stroke by empowering health cadres and providing referrals and treatment for people who experiencing symptoms of coronary heart disease to the community health center. The results of community service activities show that respondents at the Belimbing Community Health Center have a high risk of cardiovascular disease, both ACS and stroke because the average abdominal circumference of respondents is 91.34 cm, the lowest value is 75 cm and the highest value is 120 cm. when compared to the Kuranji health center. Abdominal circumference of more than 90 cm indicates that the patient is obese and is a risk factor for cardiovascular emergencies. Conclusion: the people at the Kuranji Community Health Center and the Belimbing Community Health Center have risk factors for cardiovascular emergencies.